In Search of Urban Commons Through Squatting: The Role of Knowledge Sharing in the Creation and Organization of Everyday Utopian Spaces in Sweden - Polanska, Dominika V.; Weldon, Timothy (PARTECIPAZIONE E CONFLITTO, 2020)
This study bridges research on squatting and urban commons by studying squatting - when collectively self-organized for community wide social (material and immaterial) benefit and within largely anti-capitalist and anarchist ways - as a practice of commoning. In this paper we analyze the "why" and "how" of such a practice in a Swedish context. A country where the provision of community spaces has historically been satisfied by public authorities within a contradictory hybrid model of corporatist/state capitalism amidst a traditionally well-developed public service sector and strong civil society. Our empirical material consists of 17 semi-structured interviews with squatters, as well as the authors’ participant observation at the longest lasting squats in the Swedish capital since 2000. We focus on how the creation of this ’free and voluntary’ community led to a ’commoning’ of knowledge and skills within squatters’ daily lives; and how these practices developed, evolved, and were maintained. Our analysis shows that while the space, most objects in it, and the provisioning of goods there were commoned; the most profound ’commoning’ there was immaterial in nature. This commoning centered on the un/intentional sharing, diffusion, and commoning of knowledge, skills, and even emotions and feelings which happened within the mixture of planned and autonomously rotating responsibilities in space.